Climate and Land Use Effects on Hydrologic Processes in a Primarily Rain‐Fed, Agricultural Watershed. (2nd July 2019) - Phung, Quang A.; Thompson, Allen L.; Baffaut, Claire; Costello, Christine; Sadler, E. John; Svoma, Bohumil M.; Lupo, Anthony; Gautam, Sagar
Abstract: Anticipating changes in hydrologic variables is essential for making socioeconomic water resource decisions. This study aims to assess the potential impact of land use and climate change on the hydrologic processes of a primarily rain‐fed, agriculturally based watershed in Missouri. A detailed evaluation was performed using the Soil and Water Assessment Tool for the near future (2020–2039) and mid‐century (2040–2059). Land use scenarios were mapped using the Conversion of Land Use and its Effects model. Ensemble results, based on 19 climate models, indicated a temperature increase of about 1.0°C in near future and 2.0°C in mid‐century. Combined climate and land use change scenarios showed distinct annual and seasonal hydrologic variations. Annual precipitation was projected to increase from 6% to 7%, which resulted in 14% more spring days with soil water content equal to or exceeding field capacity in mid‐century. However, summer precipitation was projected to decrease, a critical factor for crop growth. Higher temperatures led to increased potential evapotranspiration during the growing season. Combined with changes in precipitation patterns, this resulted in an increased need for irrigation by 38 mm representing a 10% increase in total irrigation water use. Analysis from multiple land use scenarios indicated converting agriculture to forest land can potentially mitigate the effects of climate change on streamflow, thus ensuring future water availability. Abstract : Research Impact Statement : Seasonal changes in climate are expected to increase irrigation requirements and reduce the number of field‐work days. Land use changes may mitigate or amplify these impacts on stream‐ and baseflow.